An Exploratory Study on Stressors Factors Among Students at Multimedia University: A Case of MMU Malacca Campus - Nor Fauziana, Ibrahim (2011)
The purpose of this study was to determine the relationships between identified stressors factors among students at Multimedia University, Melaka Malaysia. A study of stress, especially an approach towards enhancing an understanding and knowledge of how the education system and cultural norms could affect personal and academic tasks in university and provide input for administrative to formulate strategy to combat stress. So, an attempt to study this condition, starting with normal adolescents, is the purpose of this study. This study had three main objectives. The first objective was identify the highest types of stress among students in Centre for Diploma Programme (CDP) MMU Malacca. The second objective was exploring the relationship between identified stressors and students successful the third objective was to assist management staff to help students find the necessary solutions (stress management programs) to ensure students successful in personal and academic development.The subjects of the study comprised of 216 students from CDP MMU Malacca campus. This study used the survey method by adapting survey questionnaire from the University Student Stress - Burge's (2009). The study showed that 89.7 percents students experienced stress, and 10.3 percent students' not experiencing stress. Using logistic regression test, the findings of the study indicates that there are many other factors influences students' stress such teaching quality/relations with lecturers, financial and environmental (campus and administrative) of the students which is can give impact in students life. Investigating the different areas where stress occurs can help students learn ways to cope with their stress.